Tanya Bray letter to Thomas Kent regarding bird sightings, Fall 1985 - Bray, Tanyaet al (1985)
Letter discusses IOU and NOU meetings and includes an annotated list of birds sighted by Tanya Bray and others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1985. Epson - sheet feed